Recent Advances in Demand Responsive Transport: Opportunities With Autonomous Bus Service—A System-of-Systems Overview - Sajid Fadlelseed; Pouria Sarhadi; Soodamani Ramalingam; Hock C. Gan; Pandelis Kourtessis; Gav Jackman; Atziri Guadalupe Sanchez Contreras; Javier Guimera Tena; James West; Jack Holland; Alice Missler (IEEE Access)
This study explores recent advancements in emerging technologies for Demand Responsive Transport (DRT), focusing on the potential integration of autonomous bus services. We review the historical development and current state of research, extending the discussion into the era of Connected and Automated Mobility (CAM), particularly in mass transit. Key components of modern DRT systems are categorised from multiple perspectives, including vehicle types, infrastructure, devices, simulation approaches, decision-making algorithms, and optimisation factors. Each element is discussed in detail, supported by comparative tables to help readers interpret the results effectively. Our findings highlight the growing interest and ongoing research in this promising domain. We identify common practices across studies and areas needing improvement. To support this, we propose a System-of-Systems (SoS) approach to evaluate the technological maturity of DRT solutions, in line with our ongoing project. A System Readiness Level (SRL) analysis is performed by identifying constituent systems and assessing their Technology Readiness Levels (TRLs) and Integration Readiness Levels (IRLs). The study also explores the deployment of DRT in a specific use case: the Maylands Business Park in Hertfordshire, UK. It aims to serve as a comprehensive reference for addressing various dimensions of DRT in mass transit, particularly in the context of automation. It offers insights into current progress and outlines opportunities for deploying DRT as a cost-effective, scalable solution to improve sustainability in Intelligent Transportation Systems (ITS).